A historical review of the techniques of recovery of parasites for their detection in human stools - Soares, Felipe Augusto; Benitez, Aline do Nascimento; Santos, Bianca Martins dos; Nery Loiola, Saulo Hudson; Rosa, Stefany Laryssa; Nagata, Walter Bertequini [UNESP]; Inacio, Sandra Valeria [UNESP]; Nagase Suzuki, Celso Tetsuo; Saraiva Bresciani, Katia Denise [UNESP]; Falcao, Alexandre Xavier; Gomes, Jancarlo Ferreira (Soc Brasileira Medicina Tropical, 2020)
Since the early 20th century, the detection of intestinal parasites has improved with the development of several techniques for parasitic structures recovery and identification, which differ in sensitivity, specificity, practicality, cost, and infrastructure demand. This study aims to review, in chronological order, the stool examination techniques and discuss their advantages, limitations, and perspectives, and to provide professionals and specialists in this field with data that lays a foundation for critical analysis on the use of such procedures. The concentration procedures that constitute the main techniques applied in routine research and in parasitological kits are a) spontaneous sedimentation; b) centrifugation-sedimentation with formalin-ethyl acetate; and c) flotation with zinc sulfate solution. While selecting a technique, one should consider the purpose of its application and the technical-operational, biological, and physicochemical factors inherent in the procedures used in stool processing, which may restrict its use. These intrinsic limitations may have undergone procedural changes driven by scientific and technological development and by development of alternative methods, which now contribute to the improvement of diagnostic accuracy.
Keywords: Parasitology; Intestinal diseases; Historical aspects; Routine diagnostic test